Preimplantation genetic testing for aneuploidy: A Canadian Fertility and Andrology Society Guideline. Issue 1 (January 2021) - Chan, Crystal; Ryu, Michelle; Zwingerman, Rhonda
Abstract: The objective of this guideline from the Canadian Fertility and Andrology Society is to synthesize the evidence on preimplantation genetic testing for aneuploidies (PGT-A) using trophectoderm biopsy and 24-chromosome analysis and to provide clinical recommendations using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework. To date, randomized controlled trials have been limited to good-prognosis patients who were able to generate two or more blastocysts for biopsy. In this specific population the GRADE analysis of PGT-A shows an increase in the implantation rate and ongoing pregnancy or delivery rate per transfer. Clearly, it is difficult to generalize from this subgroup of patients to the infertility population at large. As a result, the application of PGT-A should be individualized, and patient factors such as age and ability to generate embryos will influence decision-making. Comprehensive patient counselling and informed consent are imperative before undertaking PGT-A. Potential benefits must be weighed against the costs and limitations of the technology, including the risk of embryo damage, false positives, false negatives and the detection of embryonic mosaicism. Future research is required, especially with regard to the use of PGT-A in poorer prognosis patients, and with respect to reporting outcomes per cycle start and cumulatively per retrieval.